THOMAS KUHN DAN TRADISI-INOVASI DALAM LANGKAH METODOLOGIS RISET ILMIAH - Sonjoruri Budiani Trisakti (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractThomas Kuhn divides scientific movement into normal science and revolutionary science. There is a difference between the type of scientific methodological research in normal scienceand that in revolutionary science. Scientists during normal science conduct their research activities restricted on the box of paradigmshared with the result that scientific research in normal science are always progressive in terms of cumulative progress. Scientists are tied to the tradition of paradigm-shared, and they difficult to release their dependence upon the paradigm-shared moreover to make innovation to the paradigm. Meanwhile, scientists during revolutionary science conduct their research activities based on the observations, experiments, and idea beyond the generally accepted paradigm which becomes questionable because of its failure to solve the crisis. Scientific research in revolutionary science is always progressive in terms of non-cumulative progress. Scientists become innovated person who see the crisis from a new perspective rather than from the tradition of the old-paradigm.Keywords: paradigm, normal science, scientific revolution